Radiological and Long-Term Functional Outcomes of Displaced Distal Clavicle Fractures. Issue 2 (February 2023) - Srinivasan, Ananth; Haque, Aziz; Kheiran, Amin; Singh, Harvinder Pal
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To investigate radiological and long-term functional outcomes in modified Neer 2a, 2b, and 5 distal clavicle fractures. Design: Retrospective cohort study. Setting: A single university teaching hospital. Patients/Participants: One hundred fifteen patients sustaining displaced distal clavicle fractures between January 01, 2010 and December 12, 2017. Intervention: Operative versus nonoperative management. Main Outcome Measurements: Radiographs were reviewed for fracture management and union. A customised questionnaire consisting of QuickDASH (Disabilities of the Arm, Shoulder and Hand), work, sports/performing arts, global satisfaction, and complication modules was used to determine functional outcome. Results: One hundred fifteen patients were included [mean age of 49 (18–89) years]. Thirty-three (29%) underwent early fixation (<6 weeks from injury) and were younger (37 vs. 53 years, P < 0.0001). Radiographs were available for 96 patients. Nonunion rate was 55% (53/96), and majority had undergone initial nonoperative management (49 vs. 4, P < 0.00001). Eleven patients with symptomatic nonunion were deemed appropriate for delayed fixation with all cases uniting. Of the operatively managed patients, 27% (12/44) underwent metalwork removal. There were no differences in functional outcome between operative versus nonoperative and union versus nonunion patient groups at a mean follow-up of 79 months ( P > 0.05). Conclusion: Functional outcome and patient satisfaction at long-term follow-up were similar regardless of operative fixation or radiological union. Nonunion in displaced distal clavicle fractures seemed to cause minimal functional deficit in most elderly sedentary individuals, or the outcome measures were not sensitive enough to capture these differences. An individualized approach should be adopted, with less active, comorbid, and elderly patients counseled regarding the minimal functional improvement of surgery and risk of reoperation. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.